Enhancing Problem-solving Ability and Written Communication Skills through Ethnochemistry-integrated Problem-based Learning - Mamluaturrahmatika, Annisa; Suwardi, Suwardi (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aims: (1) to know the problem-solving ability of the experimental group and the control group; (2) to know the written communication skills of the experimental group and the control group; (3) to know the effective contribution of ethnochemistry-integrated Problem-based Learning (PBL) model to problem-solving ability; (4) to know the effective contribution of ethnochemistry-integrated PBL model to written communication skills. This research used a quasi-experiment model with a posttest-only design. Data were analyzed an independent samples t-test & independent samples effect sizes. The results showed: (1) there is a significant difference in problem-solving ability between the experimental group and the control group; (2) there is a significant difference in written communication skills between the experimental group and the control group; (3) the implementation of ethnochemistry-integrated PBL model gives a strong effect of 1.034 on problem-solving ability; (4) the implementation of ethnochemistry-integrated PBL model gives a strong effect of 1.136 on written communication skills. The implementation of ethnochemistry-integrated PBL can be useful and applied in learning as an innovation with teachers as facilitators and students as the focus of learning in other chemical materials.